The impact of differentiated learning in team-based project on undergraduate students' design thinking mindset - Astriawati, Fitri; Siburian, Jodion; Mardiyanti, Lely (JPBIO (Jurnal Pendidikan Biologi), 2024)
Rapid advancements in science and technology necessitate that universities prepare students to be adaptable, flexible, and globally competitive through the mastery of design thinking. This study aims to determine the impact of differentiated learning in team-based projects (TBPj) in improving students’ design thinking mindsets. The research methodology employed was a quasi-experimental design, with a non-equivalent post-test control group. The research sample comprised Jambi University Biology Education students selected using a purposive sampling technique. Student design thinking mindset was assessed using a questionnaire consisting of 84 statements and analyzed using the Mann-Whitney U-test. The results indicated that the control class design thinking mindset score (Mdn = 321.00) was significantly lower than that of the experimental class (Mdn = 374; U = 115.500, p < 0.001, r = 0.67). Based on these findings, it can be concluded that the implementation of differentiated learning in team-based projects (TBPj) has a high impact on improving students’ design thinking mindset.